Analyzing super-enhancer temporal dynamics reveals potential critical enhancers and their gene regulatory networks underlying skeletal muscle development - Zhang, Song; Wang, Chao; Qin, Shenghua; Chen, Choulin; Bao, Yongzhou; Zhang, Yuanyuan; Xu, Lingna; Liu, Qingyou; Zhao, Yunxiang; Li, Kui; Tang, Zhonglin; Liu, Yuwen

(untitled) (Genome Research, 2024)
Super-enhancers (SEs) govern the expression of genes defining cell identity. However, the dynamic landscape of SEs and their critical constituent enhancers involved in skeletal muscle development remains unclear. In this study, using pig as a model, we employed cleavage under targets and tagmentation (CUT&Tag) to profile the enhancer-associated histone modification marker H3K27ac in skeletal muscle across two prenatal and three postnatal stages, and investigated how SEs influence skeletal muscle development. We identify three SE families with distinct temporal dynamics: continuous (Con, 397), transient (TS, 434), and de novo (DN, 756). These SE families are associated with different temporal gene expression trajectories, biological functions, and DNA methylation levels. Notably, several lines of evidence suggest a potential prominent role of Con SEs in regulating porcine muscle development and meat traits. To pinpoint key cis-regulatory units in Con SEs, we developed an integrative approach that leverages information from eRNA annotation, genome-wide association study (GWAS) signals, and high-throughput capture self-transcribing active regulatory region sequencing (STARR-seq) experiments. Within Con SEs, we identify 20 candidate critical enhancers with meat and carcass-associated DNA variations that affect enhancer activity, and infer their upstream transcription factors and downstream target genes. As a proof of concept, we experimentally validate the role of one such enhancer and its potential target gene during myogenesis. Our findings reveal the dynamic regulatory features of SEs in skeletal muscle development and provide a general integrative framework for identifying critical enhancers underlying the formation of complex traits.